Transient hydrodynamic analysis of the transition process of bulb hydraulic turbine. (December 2015) - Li, Yiming; Song, Guiqiu; Yan, Yunlei
Highlights: Dynamic mesh was applied to simulate transition process of bulb hydraulic turbine. Established parameters describing the dynamic characteristics of the bulb turbine. Revealed the variations of pressure and flow in the transition process. Abstract: In this paper, a semi-implicit method for solving pressure coupled equations used to calculate the flow field, and dynamic mesh were employed to simulate the three-dimensional dynamic turbulent flow of whole flow channels, in start transition process and runaway transition process of bulb hydraulic turbine. In above processes, the transition process of pressure field and flow field were realistically modeled and simulated, which reflects the influence of water flow state, after passing through guide vanes on the inflow of the runner blades, and reveals the flow field variations in the transition process. The numerical results show that: during the start transition process, with the increase of guide vane opening, the flow circulation produced by water flowing through the guide vanes becomes smaller; therefore, the rotational acceleration of the runner decreases and the rotational speed value reduces. In the runaway transition process, the hydraulic turbine operating with load has a sudden load rejection and then, the hydraulic turbine rotational speed is rising with the guide vane closing, leading to pressure pulsations and severe vortex phenomenon, which will cause significant vibrations of swings.